2021
DOI: 10.1111/jop.13167
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of oral mucosal lesions in patients with pemphigus vulgaris: A systematic review and meta‐analysis

Abstract: Objective To assess the prevalence of oral mucosal lesions in patients with Pemphigus Vulgaris. Methods Observational studies reporting the prevalence of oral lesions in pemphigus vulgaris patients, without restriction to language and year of publication, were selected in a two‐phase process. Search strategies were applied to PubMed, Scopus, Livivo, Web of Science, LILACS, Google Scholar, and OpenGrey databases. Articles assessing the prevalence of oral lesions in patients with conditions other than pemphigus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
(95 reference statements)
0
10
0
Order By: Relevance
“…There are two clinical forms of pemphigus vulgaris: mucosal (MPV) and mucocutaneous (MCPV) which patients' mucosa is affected and over five skin lesions are present 2 . The recent study showed that patients with pemphigus vulgaris have oral lesion about 90% with solely oral mucosal lesion around 50% 3 . The presentation symptoms include tenderness in the throat, pain on swallowing, hoarseness, or dysphonia 2 .…”
Section: Introductionmentioning
confidence: 99%
“…There are two clinical forms of pemphigus vulgaris: mucosal (MPV) and mucocutaneous (MCPV) which patients' mucosa is affected and over five skin lesions are present 2 . The recent study showed that patients with pemphigus vulgaris have oral lesion about 90% with solely oral mucosal lesion around 50% 3 . The presentation symptoms include tenderness in the throat, pain on swallowing, hoarseness, or dysphonia 2 .…”
Section: Introductionmentioning
confidence: 99%
“…The first site of involvement in two-thirds of PV patients is the oral mucosa [ 6 , 7 ]. Nevertheless, in most cases in which cutaneous lesions develop first, oral lesions will ultimately arise [ 6 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The first site of involvement in two-thirds of PV patients is the oral mucosa [ 6 , 7 ]. Nevertheless, in most cases in which cutaneous lesions develop first, oral lesions will ultimately arise [ 6 , 8 ]. The mortality rate of PV has decreased in recent years due to therapeutic advances [ 9 ], but it is still an important cause of significant mortality [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations